Indications of Discrimination in Regional Regulation Against Migrants in Bali (Bali Regulation Number 4 of 2019) - Nova Effenty Muhammad; Zulfitri Zulkarnain Suleman (Khazanah Sosial, 2023)
This study aims to find out the background of the formation of Peraturan Daerah (Regional Regulation – Regional Regulation) Number 4 of 2019. The researcher found that there is an effort by the Bali provincial government to provide a legal umbrella to the Customary Village in regulating its citizens and forming awig-awig or village rules respectively as a customary village. But the migrants in Bali who are mostly Muslims in Bali feel this is a form of discrimination. To analyze this problem the author uses qualitative research. Primary data sources are from the Bali Provincial Legal Bureau, from the Village Development Office, Traditional Village administrators, and migrants in Bali.  Meanwhile, migrants on the island of Bali, the majority of whom are Muslims, feel that the Adat Village regulation as the embodiment of Regional Regulation Number 4  of 2019 is a discriminatory regional regulation because it provides a legal umbrella for the implementation of fees/collections carried out by Adat Villages in Bali. There is also competition or competition such as in the economic field, migrants or tamiu who live in Bali to try their luck and make a living are considered obstacles for residents. The 2011 bombing incident was also the peak of the conflict because the perpetrators were migrants/tamiu in Bali.  This research finds that the relationship between Islam and Hinduism in Bali appears to be harmonious, but in fact it is shrouded in several hidden conflicts called Pragmatic Tolerance. The contribution of this research is expected to benefit the meaning of religious moderation in the scheme of real religious tolerance in Indonesia.